Hepatitis B Antigenaemia, Nephrotic Syndrome and Pulmonary Embolism A Series of Unfortunate Events: A Case Report - Muhammad Hassaan Malik (22392544) (2025)
Hepatitis B is a major health concern. It primarily affects the liver, but it can also cause systemic complications like antigenaemia and nephrotic syndrome. Nephrotic syndrome causes proteinuria, hypoalbuminaemia, oedema, hyperlipidaemia and hypercoagulability. This hypercoagulable state may lead to a life‐threatening complication of nephrotic syndrome: thromboembolism. This case report presents a rare medical case where a patient with chronic HBV develops nephrotic syndrome and subsequent pulmonary embolism. The co‐occurrence of these diseases in a single patient highlights the importance of their intricate pathology. By examining this unique case, we aim to highlight the diagnostic and therapeutic challenges in such clinical presentations, providing valuable insight for professionals dealing with similar cases. Other Information Published in: Respirology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/rcr2.70145